EFEKTIVITAS KONSELING KOGNITIF SOSIAL TEKNIK BERMAIN PERAN UNTUK MENINGKATKAN SELF AFILIASI - Widyanti, Andita; Dharsana, I Ketut; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2019)
This study aims to improve self affiliation with social cognitive counseling role playing techniques in class X UPW A SMK N 1 Singaraja. This type of research is quasi-experimental research. The sampling technique uses random sampling. Self-affiliated data were collected by questionnaire. The analytical method used is Independent Sample Test using the JASP Version 0.7.5.5 software program. and continued with d?Cohen to calculate the level of effectiveness. The results showed that there were differences in the self-affiliation of the experimental group students after taking treatment with the self-affiliated control group, l obtained t = 4.791 with p <0.001 then p <0.05. Testing Effect Size (ES) through d?Cohen also shows the level of effectiveness of the high social cognitive counseling model (ES = 1,145). These results prove that social cognitive counseling with role playing techniques is effective for improving self-affiliation of class X students of UPW A SMK N 1 Singaraja.Keywords: Self Afiliasi, Social Cognitive Counseling, Role Playing Techniques, Lesson Study